Do Trade Openness and FDI Drive Economic Growth in MENA ‎Countries? Insights from A Panel ARDL Approach - Oussama, Ritahi; Amine, Dafir; Abdelouahad, Es-sabir; Abdellah, Echaoui; Mohamed, Mansouri (International Journal of Accounting and Economics Studies, 2025)
Against the backdrop of persistent growth disparities and economic volatility in the Middle East and North Africa (MENA) region, under-‎standing the role of external flows such as foreign direct investment (FDI) and trade openness has become increasingly crucial. This study ‎investigates the dynamic linkages between economic growth, FDI, trade openness, and key macro-financial variables—namely domestic ‎credit, gross fixed capital formation, and inflation—across 17 MENA countries over the period 1990–2023. Employing PMG, MG, DFE, ‎and their Common Correlated Effects variants (CCE–PMG, CCE–MG)—the analysis addresses heterogeneity and cross-sectional dependence. Empirical findings reveal that FDI and trade openness exert significant positive effects on long-run GDP growth, while domestic credit negatively affects growth in the short run. Long-run effects of fixed capital formation and inflation vary across models, underscoring ‎structural differences. The robustness of results under CCE estimators confirms the importance of correcting for global shocks. The study ‎underscores policy implications: enhancing absorptive capacity, targeting quality FDI in manufacturing, deepening export diversification, ‎reinforcing institutions, and coordinating regional economic policies to sustainably leverage external flows for long-term growth‎.